The PtdIns3‐phosphatase MTMR3 interacts with mTORC1 and suppresses its activity. Issue 1 (31st December 2015) - Hao, Feike; Itoh, Takashi; Morita, Eiji; Shirahama‐Noda, Kanae; Yoshimori, Tamotsu; Noda, Takeshi
Abstract : Macroautophagy is a major intracellular degradation system. We previously reported that overexpression of phosphatase‐deficient MTMR3, a member of the myotubularin phosphatidylinositol (PI) 3‐phosphatase family, leads to induction of autophagy. In this study, we found that MTMR3 interacted with mTORC1, an evolutionarily conserved serine/threonine kinase complex, which regulates cell growth and autophagy in response to environmental stimuli. Furthermore, overexpression of MTMR3 inhibited mTORC1 activity. The N‐terminal half of MTMR3, including the PH‐G and phosphatase domains, was necessary and sufficient for these effects. Phosphatase‐deficient MTMR3 provided more robust suppression of mTORC1 activity than wild‐type MTMR3. Furthermore, phosphatase‐deficient full length MTMR3 and the phosphatase domain alone were localized to the Golgi. These results suggest a new regulatory mechanism of mTORC1 in association with PI3P. Abstract :